The Effect of Core Stability Exercise on Myogenic Lower Back Pain: A Systematic Review - Al'Arifi, Afthon Aziz; Sudaryanto, Wahyu Tri (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Introduction: Myogenic low back pain is a sign of pain, muscle spasm, and limited functional activities. This disease can be treated with core stability exercise, which is a form of active exercise designed to strengthen muscles and increase stability to support the spine and help prevent lower back pain. However, until now there has been no literature discussing the effect of core stability exercise on myogenic low back pain. Methods: A systematic search was conducted through PubMed, ScienceDirect, and Cochrane Library to identify studies examining the effect of core stability exercise on myogenic lower back pain. Results: There were 6 pre and post test control group studies with a total 143 patients that met inlclusion criteria. All existing studies show that core stability exercise can reduce NRS, ODI, VAS, and QVAS significantly (p<0.05) and increase flexibility scores significantly (p<0.05). The frequency of intervention was between 8-12 times for 4-8 weeks. Conclusion: Core stability exercise had a significant effect in reducing pain and increasing functional capacity in myogenic low back pain patients.